Prospects on Cattle Based Crop-Livestock Systems for The Irrigated Paddy Field in Lombok - Sembiring, Hasil; Panjaitan, Tanda; ., Mashur; Praptomo, Dwi; Muzani, A; Sauki, A; ., Wildan; ., Mansyur; ., Sasongko; A, Nurul (Indonesian Animal Sciences Society, 2002)
Grouped livestock management is one of the characteristic animals raising in Lombok. In the year of 2000, there were 1096 farmers group that had a very potential opportunity to optimize the livestock productions through the crop-livestock systems approach. The assessment of this approach for the irrigated paddy field area has being conducted in the village of Sepakok, sub- district of Pringgarata, district of Lombok Tengah. The objective of the study was to improve the efficiency and sustainability of the crop-livestock system as well as environmentally friendly issues. A total of 112 household farmers were involved in the study, joined in the